Bilateral Sensorineural Deafness in a Young Pregnant Female Presenting with a Fever: A Rare Complication of a Reemerging Disease—Spotted Fever Group Rickettsioses - A. G. T. A. Kariyawasam; D. R. Palangasinghe; C. L. Fonseka; P. U. T. De Silva; T. E. Kanakkahewa; N. J. Dahanayaka (Case Reports in Infectious Diseases)
Background. Rickettsial illnesses are a group of arthropod-borne remerging diseases. They are subdivided into three groups as typhus, spotted fever, and scrub typhus group. Complications such as reversible bilateral deafness due to spotted fever rickettsioses are infrequently reported in the literature. Case Presentation. We present a young pregnant female who developed bilateral sensorineural deafness on the fifth day of an acute febrile illness with a maculopapular rash. Rickettsia conorii IgG (>1/450) became highly positive, and she received oral azithromycin for ten days with complete resolution of fever and rash. The sensorineural deafness slowly improved over several months. Conclusion. Sensorineural deafness is a rare complication of spotted fever group rickettsioses. Since usage of doxycycline is controversial in pregnancy, azithromycin gave a favourable recovery of fever. Sensorineural deafness took several months to resolve after completion of antibiotics.